Evaluation of seasonal variation of vitamin D levels according to demographic criteria (Annals of Medical Research, 2021)
Aim: Although vitamin D can be taken with nutrients, it is substantially synthesized in the skin tissue under the influence of the ultraviolet ray which comes from the sunlight. Therefore, the increase in the expression of vitamin D in the body during periods of increased sunlight can be expected. In this study, it was aimed to determine whether the change in the serum vitamin D levels of the patients who applied to Uşak Training and Research Hospital were significant according to age, gender and months of the year. Material and Methods: The serum vitamin D test results of the patients aged 0-80 who applied to the outpatient clinics of the hospital between 1 January and 31 December 2018 were retrospectively obtained from the hospital automation system. Data were analyzed using SPSS 21 software. p0.05 was considered significant.Results: The largest population of 62.253 vitamin D requests is 18-65 age groups. Serum vitamin D levels were found to be 16.18±10.39 ng/ml in the whole population: 15.85±10.49 ng/ml in women and 17.18±10.03 ng/ml in men. The mean value for women was statistically lower than men (p 0.05). There was a statistically significant difference between vitamin D averages in months, the lowest mean value in January (10.74±8.58 ng / ml), the highest value in July (23.29 ±10.6 ng / ml).Conclusion: In this study, the mean levels of vitamin D were found to be insufficient even in the summer months when sunlight was the most effective. This may be due to the fact that the population may benefit from less sunlight or structural variations of the vitamin D-binding proteins in the body may affect the use of vitamin D. Therefore, extensive research is needed to determine the level of clinical effects of vitamin D deficiency.
Keywords: Adult age; sun light; Vitamin D